T cell thymic selection and peripheral homeostatic proliferation in infectious diseases - V. A. Kozlov (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
There is no doubt that infectious agents and host undergo multilayered yet not fully understood interactions. This is primarily due to at least mechanisms resulting in chronic course of infectious process. Acute infection proceeds in parallel with primary immune response and its typical phases, each of which manifests as certain stage in clinical picture featured with disease onset and subsequent recovery. A whole process of immune response developing against infectious agent occurs in peripheral lymphoid organs and immune tissues. With regard to the role of immune system in infectious process, process, two main outstanding issues still remain unanswered: 1) what are the mechanisms of host death in the case of acute infectious process? 2) what is a “fault” of immune system in it? In its inferiority or in abruptly suppressed functions induced by infectious agent, when it “does not have time” to mount an immune response of sufficient power? So far, no answer is still found yet. The second question concerns mechanisms of converting to chronic course of infectious process. The obtained available in publications evidence about an intimately involved thymus as the central immune organ in infectious process of, the main function of which is to ensure developing central immune tolerance to self-antigens accomplished via T-cell positive and negative selection. It turned out that in case of some examined infections due to pathogens, which entered the thymus, such intimate events such as partial tolerance to pathogens and autoimmune reactivity are altered. Moreover, these processes are further aggravated by homeostatic proliferation, which is also induced by an infectious agent. In both cases, it accounts for decreased magnitude of immune response against a certain pathogen, burdened by emergence of autoimmune reactions.